Evaluation of Constructability Factors on The Implementation Budget Plan Based on Importance Performance Analysis - Shalwa Norendina Aziz; I Nyoman Dita Pahang Putra; Elok Dewi Widowati; Griselda Junianda Velantika (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The rapid growth of the construction industry has increased the complexity of project implementation; however, in practice, cost overruns still frequently occur due to the suboptimal application of constructability during the planning and execution phases of projects. This situation results in a discrepancy between the planned budget and actual on-site expenditures. This study aims to identify the constructability factors that influence the implementation of the budget plan, analyze. The importance and performance levels of each factor, and evaluate the gaps as a basis for determining improvement priorities. The study employs a quantitative approach using a survey method by distributing questionnaires to contractors, followed by analysis using the Importance-Performance Analysis method. The results indicate that the average importance level of 3.737 is higher than the performance level of 3.368, suggesting that the implementation of constructability factors has not fully met the expected level of importance. A total of 16 variables had a conformity level below 100%, thus falling into the improvement priority category, while several other variables demonstrated performance that met or exceeded their importance levels. The contribution of this study lies in the integration of constructability analysis with the evaluation of the efficiency of the implementation budget plan using the IPA method to determine priorities for improving the performance of constructability factors Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and Production